Fronto-subcortical functional connectivity in patients with schizophrenia and bipolar disorder during a verbal fluency task. (15th November 2018) - Vandevelde, Anaïs; Leroux, Elise; Delcroix, Nicolas; Dollfus, Sonia
Abstract: Objectives: Impairments in language production are common of schizophrenia (SZ) and bipolar disorder (BD). Identifying distinct functional connectivity (FC) patterns in SZ and BD may provide biomarkers for their diagnoses. Methods: Forty-nine participants (15 SZ, 14 BD and 20 healthy controls (HC)) underwent a verbal fluency task consisting of mentally generating verbs in French, alternated with periods of silence. Functional network allowed identifying activation clusters: the medio-frontal cluster (MFC), the left subcortical cluster (LSCC) and the left fronto-lateral cluster (LFLC). FC was calculated between the average blood oxygen level-dependent signal time series in each cluster. Analyses of covariance were performed to test group differences on FC among the three paired-seed regions. Results: SZ presented a significant reduced FC compared to HC within two paired-seed regions between the LFLC and the LSCC and between the MFC and the LSCC while BD were not significantly different from HC. SZ compared to BD exhibited a reduced FC within one paired-seed region between the MFC and the LSCC. There was no group effect between the MFC and the LFLC. Conclusions: A specific medio-prefronto-striato-thalamic functional dysconnectivity may be implicated in the pathophysiology of schizophrenia. This reduced fronto-subcortical FC could be a functional brain biomarker of schizophrenia.